Mitochondria-Associated ER Membranes – The Origin Site of Autophagy - Yang, Ming; Li, Chenrui; Yang, Shikun; Xiao, Ying; Xiong, Xiaofen; Chen, Wei; Zhao, Hao; Zhang, Qin; Han, Yachun; Sun, Lin (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is a process of intracellular self-recycling and degradation that plays an important role in maintaining cell homeostasis. However, the molecular mechanism of autophagy remains to be further studied. Mitochondria-associated endoplasmic reticulum membranes (MAMs) are the region of the ER that mediate communication between the ER and mitochondria. MAMs have been demonstrated to be involved in autophagy, Ca2+ transport and lipid metabolism. Here, we discuss the composition and function of MAMs, more specifically, to emphasize the role of MAMs in regulating autophagy. Finally, some key information that may be useful for future research is summarized.